76.5k views
0 votes
Solve for " f "

\sf -f+2+4f=8-3f

User Zoidbeck
by
6.1k points

2 Answers

6 votes

Answer:

f = 1

Explanation:

1) Simplify -f+2+4f to 3f+2.

3f+2=8-3f

2) Subtract 2 from both sides.

3f=8-3f-2

3) Simplify 8-3f-2 to -3f+6

3f=-3f+6

4) Add 3f to both sides.

3f+3f=6

5) Simplify 3f+3f to 6f.

6f = 6

6) Divide both sides by 6.

f = 1

User Sznrbrt
by
6.5k points
6 votes

Answer:

f=1

Explanation:

first, we gather all of the f's, and numbers into seperate sides

in result we would get -f+3f+4f=8-2

we can think of this as:

-1+3+4=8-2 then add the f's later

in result we get

6f=6

we divide both sides by 6

and we get f=1 :)

User Hcharlanes
by
6.5k points